(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2021)
Wetlands serve as important natural resources and play a major eco-hydrological role in environmental management. A methodical study has been carried out to estimate physico-chemical characteristics of the selected wetlands of Dhampur which is situated 17 km away from bank of Ramganga River. It is one of the tehsil of district Bijnor, Uttar Pradesh India and comes under Moradabad division. We conducted investigation to evaluate the physicochemical and biological characteristics of wetlands in Dhampur. During investigation, ten physico-chemical water quality parameters have been analyzed. In Dhampur around 6 wetland are present where water is combining with soil. It is present in saturated form by surface of ground water. Hydrological cycle is most important example of wetland. In the study of wetland we measure the properties of water like physical or chemical property as turbidity pH value and temperature.